Undergraduate Business Analytics and the Overlap with Information Systems Programs - Ceccucci, Wendy; Jones, Kiku; Toskin, Katarzyna; Leonard, Lori (Information Systems Education Journal, 2020)
As companies continue to put data and business analytics as their top priority, universities will need to supply students with the appropriate skill sets that meet this demand and offer future opportunities to their graduates. Although business analytics is a new field, many of the required competencies stem from already established areas such as Information/Computer Technology or Information Systems. Using a sample of 225 randomly selected AACSB accredited business schools this study examined the new developments in Business Analytics undergraduate academic programs, and determined the amount of overlap between the Business Analytics and the Information/Computer Technology degree programs. Our findings reveal that approximately 36 percent of the Business Analytics programs overlap with the Information/Computer Technology programs. In addition, the top three required courses in most Business Analytics programs include a Database course, predictive analytics course, and Introduction to Business Analytics. This research provides valuable insight for schools that haven't adopted a Business Analytics degree yet or are looking to improve their existing curriculum. In addition, colleges and universities can now utilize the appropriate Information Systems courses and include them as important foundation and part of their Business Analytics programs.
Keywords: Business Administration Education; Business Schools; College Curriculum; Computer Science Education; Elective Courses; Information Technology; Required Courses; Undergraduate Study; dept.bis; peer-reviewed; ⛔ No DOI found

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed